Alterations in Pharmacokinetics of Orally Administered Carbamazepine in Rats Treated with Sodium alginate: Possible Interaction between Therapeutic Drugs and Semi-solid Enteral Nutrients - Nagai, Katsuhito; Omotani, Sachiko; Ito, Akihiko; Nishimura, Ikumi; Hatsuda, Yasutoshi; Mukai, Junji; Teramachi, Hitomi; Myotoku, Michiaki (Drug Research, 2019)
Objective The use of enteral nutrients plays an extremely important role in accurate nutrition management. Sodium alginate (SA) is frequently used for the semi-solidification of enteral nutrients. In the present study, we investigated whether the pharmacokinetic profile of orally administered carbamazepine (CBZ) is altered by a treatment with SA immediately before and after dosing of the drug. Furthermore, the adsorption effects of SA on CBZ were examined using an in vitro analysis.Method SA was orally administered to rats just before and immediately after CBZ dosing. The CBZ concentration profile following its oral administration was analyzed by a non-compartmental method. The adsorption of CBZ onto SA was evaluated after centrifugation using an ultrafiltration device.Findings The serum concentration of orally administered CBZ at each sampling point was reduced by the treatment with SA, and the extent of the decrease observed in the concentration of CBZ was larger when SA was ingested immediately after administration of the drug, which was consistent with the alteration observed in the value of the area under the curve (AUC). No significant differences were noted in the elimination rate at the terminal phase (ke) among the groups. In the in vitro assay, CBZ was adsorbed by SA in the solution used to reflect fluid in the intestinal tract.Conclusions The pharmacological efficacies of CBZ might be reduced by SA through the pharmacokinetic interactions, and that the careful attention should be paid to the timing of administration of CBZ and semi-solid enteral nutrients.
Keywords: sodium alginate-semi; solid enteral nutrient; carbamazepine; pharmacokinetic interaction; absorption